Religious Moderation Among Generation Z Indonesian Muslims: A Dialectical Analysis of Understanding and Practice - Prabowo Adi Widayat; Cahaya Khaeroni; Kuliyatun Kuliyatun (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This article examines the narrative patterns of the Islamic Generation Z in Metro, Indonesia, with a focus on the interplay between understanding and the practice of religious moderation. The discussion is motivated by the significant influence of Islamic discourse in both the virtual and real lives of this generation. This influence is evident in the diverse Islamic studies disseminated by individuals from this demographic, as well as by scholars, ustāż, ulema, and kiai, through pengajian ‘religious gatherings’ and various digital Islamic platforms such as www.muhamamdiyah.or.id, NU Online, Islam Digest on Republika Online, www.muslim.or.id, islami.co, YouTube, and others. This Islamic discourse functions as a barometer for Generation Z Muslims, guiding them in the proper and proportional practice of their faith in everyday life. To foster a robust understanding of Islam, Generation Z requires a framework that considers their level of comprehension and the ease of practice. In reality, they often face challenges in sifting through the diverse information available to them, making it difficult to use it as a reliable guideline for their actions, speech, and thoughts. The findings presented in this article stem from field research utilizing a single instrumental case study approach. Data collection methods included non-participant observation, in-depth interviews, and documentation, with analysis conducted at various stages of the research process. The results reveal two distinct types of Islamic narratives among Generation Z. The first is the functional dialectical narrative, which is grounded in logical, empirical, and methodological scientific studies and is effectively applicable in religious and social interactions within a pluralistic society. The second type is relational dogmatism, characterized by a religious narrative rooted in binding and fundamental textual arguments (fiqhiyyah-muqayyadah). This narrative serves as a singular guideline for spiritual and social interactions in a pluralistic context.